Hubungan Motivasi Belajar dan Perhatian Orang Tua dengan Hasil Belajar Matematika Siswa SMP - Latifah Aldin Fajrina; Tri Astuti Arigiyati; Fitria Sulistyowati (UNION : Jurnal Ilmiah Pendidikan Matematika, 2022)
This research aims to determine positive and significant connection between learning motivation and parents attention with mathematics learning results of class IX SMP Negeri 1 Lendah partially and simultaneously. This type of research is correlational research. Population this research is 191 students, the sample searched by simple random sampling technique. Data learning motivation and parents attention collected by questionnaire, and students mathematics learning results obtained by documentation. The data then analyzed by t-test and F-test to determine the connection partially and simultaneously. The results showed a positive and significant connection between learning motivation with mathematics learning results; there is a positive but not significant connection between parents attention with mathematics learning results; and there is a positive and significant connection between learning motivation and parents attention with mathematics learning results.